GAMBARAN TINGKAT KECEMASAN PERAWAT RUANG ISOLASI MENGENAI RISIKO PENULARAN COVID-19 DI RUMAH SAKIT S - Suci Purnama Rizkiyani, - (2021)
Background: Currently the world is being hit by a health crisis with the increasing number of illnesses and the number of deaths due to the COVID-19 virus. This resulted in the emergence of new problems for the community, including for nurses as the vanguard to handle this case. The high workload experienced by nurses, many of whom experience physical and psychosocial fatigue. One of the psychosocial problems experienced by nurses is anxiety. Anxiety is a feeling that is not clearly felt by someone such as anxiety, worry accompanied by a response. Purpose: The purpose of this study was to describe the level of anxiety of the isolation room nurses regarding the risk of transmission of COVID-19 at S. Hospital. Methods: This study used a descriptive research design withmethod survey an online. The data collection technique used an anxiety level questionnaire instrument from the Zung-Self-Rating Anxiety Scale. Sampling using nonprobability sampling technique with the number of respondents 52 nurses who have met the inclusion and exclusion criteria. Result: The results of this study indicate that respondents who experienced mild anxiety levels were 34 respondents (65.4%), respondents who experienced moderate levels of anxiety were 17 respondents (32.7%) and only 1 respondent (1.9%) experienced severe anxiety. Conclusion: The general description of the anxiety level of the isolation room nurses is that more nurses experience mild anxiety, this is because all respondents have received vaccinations, always apply health protocols and wear complete APD according to standards when treating patients, so this can reduce the risk of transmission. and can reduce anxiety well.